P243 Case series of Cryptococcal Meningitis—Experience in North Western India over 1 year (2021–22). (20th September 2022) - Naguthevar, Santhanam; Garg, MK; Bohra, Gopal Krishna; Jain, Vidhi; Kumar, Deepak; Midha, Naresh Kumar; Meena, Durga Shankar; Sharma, Shivang; R, Akshatha; Singh, Kuldeep; Kombade, Sarika P
Abstract: Poster session 2, September 22, 2022, 12:30 PM - 1:30 PM:   Objective: Cryptococcosis is an opportunistic fungal infection causing high morbidity and mortality in patients, preferentially affecting immunocompromised. It can cause a wide array of clinical manifestation, which includes meningitis, pulmonary, as well as disseminated infection. Cryptococcus neoformans causes more than 90% cases of cryptococcal meningitis. Methodology: We performed a retrospective review of patients with confirmed cryptococcal meningitis during 1 year period from 2021 to 2022 in tertiary care center, AIIMS Jodhpur. We assessed clinical, radiological, microbiological, and biochemical parameters along with treatment provided and outcomes of the patient. Results: Of 189 patients screened for suspected cryptococcal meningitis, 6 were microbiologically confirmed positive. All the patients were immunocompromised, of which four were HIV positive and one was a solid organ transplant recipient on immunosuppression and one was old TB Meningitis. Most common symptom was headache and altered sensorium (100%). Radiological findings showed 30% had no significant abnormality. CSF examination revealed average CSF protein 97.6 (63-163), CSF chloride 103.3 (108-132), sugar 36.33 (1-68), with predominant lymphocytes. All the patients were microbiologically confirmed by CSF cryptococcal latex test. A total of 4/5 patients received amphotericin B (3 mg/kg) with fluconazole (1200 mg) for 2 weeks in the induction phase followed by fluconazole consolidation phase and maintenance phase. Of the five patients, four patients survive with a good response to the treatment with one fatality. Conclusion: Through our case series we emphasize the fact that Cryptococcal meningitidis may present with non-significant radiological features. Thus, the differential diagnosis of C. meningitidis must always be thought of when an immunocompromised patient presents with headaches and other signs and symptoms involving the central nervous system.